Pengaruh Aglomerasi, Tenaga Kerja, Pertumbuhan Penduduk, dan Investasi terhadap Pertumbuhan Ekonomi Provinsi Sumatera Utara Tahun 2015-2020 - Mei Sun Rain Anju Sasmita Batubara (Universitas Diponegoro, 2021)
The ability of a region to grow rapidly and sustainably is largely determined by various economic factors which are interrelated with each other. GRDP can be used as an indicator to measure economic growth in a region. The purpose of this study is to analyze the effect of agglomeration, labor, population growth, and investment partially or simultaneously on economic growth in North Sumatra Province in 2015-2020. The analytical method used in this study is the regression method Ordinary Least Square (OLS) using secondary data sourced from BPS, DPMPTSP, DISNAKER North Sumatra with a total of 198 observations. The data time series used are 2015-2020 and the data cross section used are 33 districts/cities in North Sumatra Province. This study uses the unbalanced panel data method with a Random Effect Model. The results in this study indicate agglomeration variables and population growth have a positive and significant effect on economic growth in North Sumatra. Meanwhile, labor and investment variables have a negative effect on economic growth in North Sumatra. Agglomeration variables, labor, population growth, and investment together have a positive and significant impact on the economic growth of North Sumatra Province in 2015-2020.